PENGARUH LITERASI KEUANGAN DAN KEMUDAHAN BERTRANSAKSI MENGGUNAKAN QRIS TERHADAP IMPULSIVE BUYING GENERASI Z DI KOTA DAN KABUPATEN TASIKMALAYA - Zalyanti, Ilma Alya; Rahayu, Intan; Pratiwi, Laras (JURNAL EKONOMI PERJUANGAN, 2025)
This study aims to determine the Effect of Financial Literacy and Ease of Transaction Using QRIS on Impulsive Buying partially. The population used in this study is Generation Z in Tasikmalaya City and Regency. The method used in this study is the associative descriptive method with a quantitative approach. Sample selection uses the Purposive Sampling method. The sample used was 100 people. The data collection method used in this study is primary data obtained from distributing questionnaires via Google Form. The data analysis technique used is multiple linear regression with the help of the SPSS Version 27 Program. The results of this study indicate that Financial Literacy has a negative effect on Impulsive Buying, and Ease of Transaction has a positive effect on Impulsive Buying. Keyword : Financial Literacy, the Ease of Transactions, Impulsive Buying.